Plastic leaf morphology in three species of Quercus: The more exposed leaves are smaller, more lobated and denser. Issue 1 (31st October 2019) - Kusi, Joseph; Karsai, Istvan
Abstract: Phenotypic plasticity and developmental instability in leaf traits are common in oak species but the role of environmental factors is not well understood. To decipher possible correlations between different leaf traits and effects of the position of leaves within the tree canopy, we quantified the plasticity of three leaf traits of 30 trees of Quercus alba L., Quercus palustris Muench and Quercus velutina Lam. We hypothesized that trees could modify the shape of their leaves for better adaptation to the variable microclimate within the canopy. Our results demonstrated that the south and north outer leaves were significantly smaller, more lobed and denser than those situated in the inner canopy. The order of leaves on the branch accounted for the plasticity of leaf traits in Q. alba only. Plasticity of lobing in Q. alba and Q. velutina depended on the height of the trees. We detected fluctuating asymmetry (FA) in all three species, but the source of variation depended on branch position in Q. velutina only. FA was more pronounced in north‐facing leaves. Plasticity of the leaf traits ranged from small to medium. Plasticity of leaf area and leaf mass per area (LMA) depended on the branch position. However, the plasticity of lobation was not affected by the location of a branch within the tree canopy. Quercus alba and Q. palustris had similar plastic responses but the plasticity of Q. velutina was significantly smaller. We concluded that individual plants detect and cope with environmental stress through vegetative organ modification. Abstract : This study examined the pattern of leaf morphological variation within three oak species to explain plasticity of leaf traits. Our results demonstrate that patterns of plastic leaf response and developmental instability depend on the location of the leaf within the canopy. We conclude that trees respond and adapt to environmental stress through modification of their leaf traits such as leaf size, leaf mass per area and lobation.